2013
DOI: 10.1111/jsbm.12026
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurship Education: Introducing the Entrepreneurship Education Project

Abstract: The Entrepreneurship Education Project (http://www.trepeducation.com) is a global, longitudinal research initiative through which university students offer entrepreneurship educators and researchers data‐driven insights into the impact of entrepreneurial education on (1) both the motivational processes underlying students' road to entrepreneurship and through the entrepreneurial process and (2) the process of identity transformation from student to entrepreneur. Rooted in Social Cognitive Career Theory, the En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
123
2
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(145 citation statements)
references
References 72 publications
10
123
2
10
Order By: Relevance
“…Schwarz et al (2009) found that the intention to start a business is influenced by students' attitudes towards entrepreneurship, change, money and their perceptions regarding the university support for entrepreneurship while Saeed, Yousafzai, Yani-De-Soriano and Muffatto, (2013) reported the impact of self-realisation, role and recognition on entrepreneurial intentions. Vanevenhoven and Liguori (2013) found that entrepreneurial outcome expectations that include financial rewards, independence/autonomy, personal rewards and family security are significantly related to entrepreneurial intentions and self-efficacy. This means that individuals are more likely to have strong intentions of starting a business and belief that they are personally capable of doing so when the act would result in the achievement of these entrepreneurial outcomes.…”
Section: Shapero and Sokol's Model Of Entrepreneurial Eventmentioning
confidence: 96%
“…Schwarz et al (2009) found that the intention to start a business is influenced by students' attitudes towards entrepreneurship, change, money and their perceptions regarding the university support for entrepreneurship while Saeed, Yousafzai, Yani-De-Soriano and Muffatto, (2013) reported the impact of self-realisation, role and recognition on entrepreneurial intentions. Vanevenhoven and Liguori (2013) found that entrepreneurial outcome expectations that include financial rewards, independence/autonomy, personal rewards and family security are significantly related to entrepreneurial intentions and self-efficacy. This means that individuals are more likely to have strong intentions of starting a business and belief that they are personally capable of doing so when the act would result in the achievement of these entrepreneurial outcomes.…”
Section: Shapero and Sokol's Model Of Entrepreneurial Eventmentioning
confidence: 96%
“…The scope of entrepreneurship programs at universities has grown dramatically over the past quarter century (Morris, Kuratko, and Cornwall 2013). Prior studies have shown that entrepreneurship programs raise the level of entrepreneurial interest among students (Peterman and Kennedy 2003;Souitaris, Zerbinati, and Al-Laham 2007;Vanevenhoven and Ligouri 2013).…”
Section: Student Start-up Activities and University Embeddednessmentioning
confidence: 99%
“…Based on the methods of other impact studies (e.g., Kolvereid and Moen, 1997;Wilson et al, 2007;Liao and Gartner, 2008;Olomi and Sinyamule, 2009;Kružić and Bulog, 2010), a structured sampling procedure with an adequate sample size for an ex ante/ex post design represents a further essential requirement for evaluating entrepreneurial narratives as an adequate teaching tool (Lorz et al 2013). In addition, because most EE studies are carried out at higher educational levels (e.g., Vanevenhoven and Liguori, 2013;Volery et al, 2013;Zhang et al, 2014), a focus on currently under-researched target groups such as students of vocational schools (Lorz et al, 2013) will enrich the academic discussion.…”
Section: Discussionmentioning
confidence: 99%